Gross Domestic Product and Health Expenditure Growth in Balkan and East European Countries-Three-Decade Horizon - Milos Stepovic; Nemanja Rancic; Nemanja Rancic; Berislav Vekic; Berislav Vekic; Viktorija Dragojevic-Simic; Viktorija Dragojevic-Simic; Stefan Vekic; Nenad Ratkovic; Nenad Ratkovic; Mihajlo Jakovljevic; Mihajlo Jakovljevic; et al. (Frontiers Media S.A., 2020)
Background: Dynamics of health care has changed over time along with development of the countries themselves. The aim of the study is to compare macroeconomic and health expenditure indicators of interest, such as total health expenditure (THE) as percentage of global domestic product, global domestic product per capita in US$, and private households' out-of-pocket payments of Balkan and Eastern European countries on health, as well as to assess their progress over the observed period.Methods: This research report represents a descriptive data analysis of indicators extracted from the European Health for All database. The data were analyzed using a linear trend and regression analysis to estimate the timeline changes.Results: Greece and Slovenia have the largest median values of global domestic product per capita throughout the whole period, and the largest increment trend was in Lithuania. Median value in out-of-pocket payment of THE was the highest in Albania and Ukraine, while the largest decrease in trend was noticed in Albania and Bosnia and Herzegovina. Bosnia and Herzegovina and Greece had the largest median value of THE as percentage of Gross Domestic Product (GDP) in the observed period, while regression trend analysis showed that Serbia had the largest increase. Most of the countries showed a significant correlation between observed indicators.Conclusion: Trends in the economy must be constantly monitored due to the fact that the population is aging and non-communicable diseases are multiplying, which requires innovations in medical treatment and pharmaceutical development.